Citizen support for the Welfare State: Determinants of preferences for income redistribution - Philipp Rehm (Wissenschaftszentrum Berlin für Sozialforschung (WZB), 2005)
This paper explores the determinants of individual level support for income redistribution by the government. It argues that there are two sources of preference formation when it comes to redistribution. People are either in favor of income redistribution because they are disadvantaged, or they favor redistribution as a means to insure against income shocks. The paper explores both logics, but focuses on the latter. Four risk factors are hypothesizes to influence an individual's preferences over income redistribution: a) structural change; b) exposure to international competition; c) specificity of skills; and d) occupational unemployment. Some of these measures are novel. The paper relies on the European Social Survey 2002/2003 in order to test the formulated hypotheses. The results show that a) skill specificity and occupational unemployment are important determinants of individual preferences over redistribution whereas b) structural change and exposure to international competition are not. – – Diese Arbeit untersucht die Ursachen von Unterstützung für staatliche Einkommens- Umverteilung, auf der individuellen Ebene. Es wird argumentiert dass es zwei Quellen für Präferenzen für Umverteilung gibt. Man ist entweder für Einkommens- Umverteilung weil man benachteiligt ist. Oder man ist dafür, weil Umverteilung als Versicherung gegen bestimmte Einkommens-Fluktuationen dient. Die Arbeit untersucht beide Quellen, konzentriert sich aber auf die Logik von Umverteilung als Risiko- Absicherung. Es werden vier Risiko-Faktoren vorgeschlagen, die einen Einfluss auf individuelle Präferenzen für Einkommens-Umverteilung einen Einfluss haben könnten: a) struktureller Wandel; b) internationale Konkurrenz; c) spezialisiertes Humankapital und d) Arbeitslosigkeit innerhalb von Berufsgruppen. Einige dieser Faktoren werden in neuartiger Weise operationalisiert. Um die formulierten Hypothesen zu testen, benutzt die Arbeit das ,European Social Survey 2002/2003'. Die Resultate ergeben dass a) spezialisiertes Humankapital und Arbeitslosigkeit innerhalb von Berufsgruppen wichtige Ursachen für Präferenzen für Umverteilung sind. Hingegen können b) struktureller Wandel und internationale Konkurrenz nicht als wichtige Faktoren für Präferenzen hinsichtlich von Einkommens-Umverteilung etabliert werden.
Keywords: D31; D72; E24; H53; 330; Public Opinion; Preferences; Redistribution; Varieties of Capitalism; Trade; Unemployment; Occupations